Penelusuran Potensi Aktivitas Antibakteri dan Antioksidan Fraksi Kulit Pohon Faloak (Sterculia quadrifida R.Br) - Rollando (Jurnal Farmasi (Journal of Pharmacy), 2015)
People on Timor island use Faloak (Sterculia quadrifida R.Br.) bark as herbal remedy to cure diseases such as liver diseases, gastroenteritis and as stamina booster. Faloak bark contains fenol, flavonoid, and terpenoid. This study aims to analyze the ability of antibacterial and antioxidant of fraction of faloak bark ethanol extract. Fraction 3 showed the highest antibacterial activity (IC50) to the bacteria B. subtilis (90.51 µg/mL), E. coli (80.12µg/mL), S.aureus (77,87 μg/mL), and S.thypi (61.23 µg/mL). Antioxidant activity test showed that fraction 2 has highest phenol content (34,16 ± 0,76 mg GAE) and antioxidant activity.